Focality of Aedes (Stegomyia) aegypti Mosquito (Diptera: Culicidae) from the Chronology to the Trend Analysis in Villa Clara Province, Cuba: A Recent Study - Rigoberto Fimia-Duarte; Ricardo Osés Rodríguez; Idalberto Machado Valenzuela; María Patricia Zambrano Gavilanes; Yamilka Rios Ruiz; Rafael Armiñana García; Frank Manuel Wilford González; Freddy Eli Zambrano Gavilanes (Issues and Development in Health Research Vol. 1, 2021)
The objective of the study was to characterize the time series and trends for the focality of the Aedes aegypti mosquito, by both months and years (2007- 2017) in Villa Clara province, Cuba. In Cuba, the incidence of these entities, both parasitic and viral, is undoubtedly a health problem , with a tendency to increase the number of cases, as well as the populations of vector organisms. The research covered the 13 municipalities of the province, as well as the number of breeding sites reported by them in the different months of the analyzed period. An observational, descriptive, ecological, retrospective and statistical study was conducted, for which all the information was collected from the work cycles established for vector surveillance and control in the universe of houses and buildings in the urban areas of the 13 municipalities. The data were organized by years and months with the Excel application of Windows. The SPSS statistical package version 19.0 (the ENTER and the ERROR methods) was used to process the data. Santa Clara, Ranchuelo, Placetas, Manicaragua, Santo Domingo, and Sagua la Grande municipalities were found to have the highest absolute frequency (Fi), something very similar for the case of the cumulative relative frequency (fai), with slight changes in relation to the position of the municipalities. The focality of the Ae. a vector, reported by months, showed a direct proportional correspondence with the one reported provincially, July through November being the months with the greatest focality. It is concluded that there are environmental and anthropic conditions that favor the establishment and maintenance of the Ae. a vector focality throughout the year in Cuba.